Computationally guided design of a new Rh catalyst for selective formic acid dehydrogenation: Validation with caution. (1st November 2019) - Guan, Chao; Zhang, Dan-Dan; Zhang, Tonghuan; Huang, Mei-Hui; Chakraborty, Priyanka; Li, Huaifeng; Yao, Changguang; Zhou, Chunhui; Hu, Jinsong; Huang, Kuo-Wei
Abstract: Formic acid possesses many desirable properties as a promising hydrogen energy carrier. Density functional theory (DFT) was utilized to design new Rh complexes with 2, 2′-biimidazoline ligands to explore their potential as catalysts for formic acid dehydrogenation. These designed complexes were prepared and examined as catalysts under various temperatures and ratios of formic acid to sodium formate. It was found that although our complexes gave a high TOF of 20, 000 h −1  at 90 °C under certain formic acid/sodium formate ratios, the dehydrogenation reaction was prematurely deactivated once 30% of the formic acid was consumed. Possible deactivation mechanisms were investigated by NMR and HRMS. Our observations suggest that while guided rational design of catalysts by DFT has much potential, the method does have limitations as evidenced by our experimental comparisons and thus pure DFT design should be conducted with caution. Highlights: A new Rh complex was designed by DFT and synthesized for formic acid dehydrogenation. The designed Rh complex showed significantly enhanced reaction rates, but a short life time. Guided rational design of catalysts using DFT has benefits but also limitations.